1998
DOI: 10.1200/jco.1998.16.2.593
|View full text |Cite
|
Sign up to set email alerts
|

Long-term pamidronate treatment of advanced multiple myeloma patients reduces skeletal events. Myeloma Aredia Study Group.

Abstract: Long-term monthly infusions of pamidronate as an adjunct to chemotherapy are superior to chemotherapy alone in reducing skeletal events in stage III multiple myeloma patients, and may improve the survival of patients on salvage therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
322
2
12

Year Published

2000
2000
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 575 publications
(347 citation statements)
references
References 24 publications
11
322
2
12
Order By: Relevance
“…Despite antiresorptive therapy, repair of existing lesions is not seen, and progressive disease is associated with new skeletal events. (8)(9)(10)(11)(12)(13) New strategies to reduce skeletal-related events and improve patient outcome are urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…Despite antiresorptive therapy, repair of existing lesions is not seen, and progressive disease is associated with new skeletal events. (8)(9)(10)(11)(12)(13) New strategies to reduce skeletal-related events and improve patient outcome are urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…8 Clinical studies have suggested that BPs may induce a reduction of the tumor burden 9 and may prolong the survival of MM patients. 10,11 We have evaluated if the combination of zoledronate (Zln), a potent antiresorptive BP, 12 and dexamethasone (Dex), which is commonly used in the treatment of MM, could strengthen the inhibition of cell growth and the induction of apoptosis in human myeloma cell lines in vitro. Here, we show that the combination of both agents results in synergistic anti-myeloma effects, providing a rationale for in vivo investigations on this therapeutical combination.…”
Section: Introductionmentioning
confidence: 99%
“…Patients receiving pamidronate had a significant reduction in both the proportion who experienced skeletal events (pathologic fractures, need for operation to treat or prevent pathologic fractures, need for radiation to bone or spinal cord compression) and the number of skeletal lesions per year. The pamidronate group also had a decreased requirement for analgesic drugs and had an improved quality of life (45). Bisphosphonates may induce apoptosis in humanmyelomacell cultures and thus exert a direct effect on multiple myeloma.…”
Section: Managementof Complicationsmentioning
confidence: 99%